2015
DOI: 10.12956/tjpd.2015.184
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Assessment and Outcome of Infants with Antenatal Hydronephrosis

Abstract: Çoğunlukla geçici olan, ancak böbrek ve idrar yolunun konjenital anomalileri (CAKUT) ile de birlikte olabilen ve aileleri endişelendiren antenatal hidronefroz (AH) konusundaki dokuz yıllık deneyimlerimizi okuyucularla paylaşmaktır. Gereç ve Yöntemler: Antenatal dönemde saptanan hidronefroz nedeniyle genel pediatri polikliniğinde Ocak 2005 ve Aralık 2013 tarihleri arasında izlenen 230 hasta retrospektif olarak değerlendirildi. Hastaların kilo, boy, kan basıncı değerleri ile laboratuvar, ultrasonografi, dimerkap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Transient hydronephrosis is seen between 41% and 88% in newborn (13,14). The regression of antenatal hydronephrosis generally occurs during in the first year of life (15). In our study, spontan resolution was observed in the majority of patients with MMIAHN during the first year of life.…”
Section: Discussionsupporting
confidence: 57%
“…Transient hydronephrosis is seen between 41% and 88% in newborn (13,14). The regression of antenatal hydronephrosis generally occurs during in the first year of life (15). In our study, spontan resolution was observed in the majority of patients with MMIAHN during the first year of life.…”
Section: Discussionsupporting
confidence: 57%